2004
DOI: 10.2169/internalmedicine.43.49
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Chronic Nonspecific Symptoms by Long-term Minocycline Treatment in Japanese Patients with Coxiella burnetii Infection Considered to Have Post-Q Fever Fatigue Syndrome

Abstract: Objective To address the presence of post-Q fever fatigue syndrome (post-QFS) in Japan, and to evaluate the efficacy of minocycline for this condition.Patients and Methods In 20 Coxiella burnetii (C. burnetii) seropositive patients with persistent nonspecific symptoms including general fatigue, low-grade fever, myalgia and arthralgia, changes in subjective symptoms, C. burnetii antibody titers and C. burnetii DNA were evaluated after antibiotic treatment.Results After treatment mainly with minocycline (100 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 21 publications
0
33
2
Order By: Relevance
“…We first reported that there are also patients with QFS, apparently due to C. burnetii infection, in Japan (4). Furthermore, we found that long-term treatment with minocycline improved their symptoms (5).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…We first reported that there are also patients with QFS, apparently due to C. burnetii infection, in Japan (4). Furthermore, we found that long-term treatment with minocycline improved their symptoms (5).…”
Section: Introductionmentioning
confidence: 84%
“…Blood samples for nested PCR assay and the detection of C. burnetii antibodies were obtained from all patients during the initial examination, and 3 months after starting treatment. The presence of antibodies to C. burnetii was determined by IF and the nested PCR method, as described previously (5). An IgG antibody titer 1 : 32 was considered to be positive (12,13).…”
Section: Methodsmentioning
confidence: 99%
“…Whether this was a failure of masking or rather a placebo effect (i.e., the majority in both groups believed they Perspective were on active therapy), and whether this would have affected the outcome of a subjective measure like fatigue, is difficult to discern. The commonality and nonspecificity of fatigue, and the observation that antibiotics may improve chronic fatigue in noninfectious or other postinfectious illnesses, raise doubts as to whether it was the elimination of B. burgdorferi that resulted in this outcome [117][118][119].…”
Section: Extended Antibiotics For the Treatment Of Post-lyme Disease mentioning
confidence: 99%
“…The cases in this article (5) are applicable and may be considered as cases of post-Q-fever fatigue syndrome. As for specific clinical symptoms and the progression of post-Q-fever fatigue syndrome, on the other hand, many reports discuss that these symptoms are persistent infections, immunological modulation after acute infection or the conditions close to chronic Q-fever; no consensus has been obtained, and it was not clarified in this article (5). As described in this article (5), however, if many cases certainly considered to have post-Qfever fatigue syndrome can be collected and analyzed, its conditions may be clarified spontaneously, and it is expected that the relationships among post-Q-fever fatigue syndrome, acute Q-fever and chronic Q-fever will be clarified.…”
mentioning
confidence: 96%